A novel translabial platform utilizing bioexcipients from Litchi chinesis for the delivery of rosiglitazone maleate - N.V. Satheesh Madhav; Abhay Pratap Yadav (Elsevier, 2013)
The aim of this study was to formulate drug-loaded bio-lipstrips using novel bioexcipients isolated from the fruit pulp of Litchi chinesis (biomaterial L) and to explore the potentiality of lip skin as a novel translabial drug delivery system. The biomaterial, prepared by a simplified economical process and purified by hot dialysis, was subjected to various physicochemical evaluations along with spectral analysis including UV, FT-IR, Mass and 1H NMR. The lipstrip formulated with the novel bioexcipients was screened for its functional properties, including filmability using a film-casting method, and bio/muco-adhesitivity using a shear-stress method, the Park and Robinson method and a rotating cylinder method. Rosiglitazone-loaded bio-lipstrips were formulated by using biomaterial L as a strip former and dextrose as a flexicizer. The formulated strips were subjected to various evaluations, including thickness, folding endurance, in-vitro release and in-vivo release. The release of rosiglitazone maleate was maintained over 24 h, which was confirmed in in-vitro and in-vivo release experiments. Our results reveal that this biopolymer possesses promising stripability as well as bio-adhesitivity. The formulated bio-lipstrips are feasible for delivering rosiglitazone maleate by translabial administration.